Should we continue to administer blind shoulder injections? - (:unkn) unknown (My University, 2016)
Amaç: Bu çalışmada omuz ağrısı olan hastalarda kör ve floroskopi rehberli eklem içi omuz enjeksiyonlarının doğruluğu ve etkinliği araştırıldı.Hastalar ve yöntemler: Çalışmaya üç aydan uzun süredir omuz ağrısı olan 17 hasta (6 erkek, 11 kadın; ort. yaş 52.6±9.9 yıl; dağılım 36-66 yıl) dahil edildi. İlk eklem içi enjeksiyonlar ön yaklaşım ile kör olarak uygulandı. Enjeksiyon sonrası iğne ucunun eklem içerisinde olduğu floroskopi ve kontrast dağılımı ile doğrulandıktan sonra işlem 3 mL lokal anestezik (prilokain ve bupivakain) ve 1 mL steroid (40 mg metilprednizolon) ile tamamlandı. İlk uygulamada kontrast dağılımının eklem dışı olduğu gözlendiğinde, ikinci enjeksiyona floroskopi eşliğinde devam edildi. İşlemin devam ettirilmesi ile tüm enjeksiyonlar eklem içi oldu. Ağrı yoğunluğu görsel analog ölçeği (GAÖ) ile ölçüldü.Bulgular: Floroskopi ile bakılan kontrast dağılımına göre, 17 omzun 11'inde (%64.7) birinci kör enjeksiyonlar eklem içi idi. Başlangıç GAÖ skoru ortalaması 7.11 idi. Klinik takiplerde birinci saatte (ortalama GAÖ: 2.35), üçüncü günde (ortalama GAÖ: 2.64) ve birinci ayın sonunda (ortalama GAÖ: 2.23) ağrıda iyileşme gözlendi. Kör ve floroskopi rehberli uygulama için hasta hazırlanma süresi dışındaki ortalama süre sırasıyla 0.8 dakika ve 4.2 dakika idi.Sonuç: Kör eklem içi omuz enjeksiyonları ucuz ve kolay uygulanabilir olsa da iğnenin eklem çevresinde değil eklem içinde olduğundan emin olmak için enjeksiyonlar floroskopi ya da başka bir rehber eşliğinde yapılmalıdır.

Objectives: This study aims to investigate the accuracy and effectiveness of blind and fluoroscopic-guided intra-articular shoulder injections in patients with shoulder pain.Patients and methods: The study included 17 patients (6 males, 11 females; mean age 52.6±9.9 years; range 36 to 66 years) with shoulder pain more than three months. First intra-articular joint injections were performed with anterior approach blindly. Following the injection and after confirming that the needle tip was intra-articular with fluoroscopy and contrast distribution, the procedure was completed using 3 mL of local anesthetic (prilocaine and bupivacaine) and 1 mL of steroid (40 mg methylprednisolone). When the contrast distribution was observed to be extra-articular at the first administration, a second injection was continued under fluoroscopy guidance. All of the injections were intraarticular with the continuation of the procedure. Pain intensity was measured with visual analog scale (VAS).Results: According to the contrast distribution viewed with fluoroscopy, first blind injections were intra-articular in 11 of the 17 shoulders (64.7%). Mean of initial VAS score was 7.11. Improved pain was observed in the clinical follow-ups at the first hour (mean VAS: 2.35), third day (mean VAS: 2.64), and at the end of the first month (mean VAS: 2.23). The mean durations for blind and fluoroscopic-guided procedures excluding patients' preparation time were 0.8 minutes and 4.2 minutes, respectively.Conclusion: Although blind intra-articular shoulder injections are inexpensive and easily applicable, injections should be performed under fluoroscopy or another guide to ensure that the needle is intra-articular, not peri-articular.
Kör omuz enjeksiyonu yapmaya devam etmeli miyiz?
Keywords: Ortopedi